Robust control of aircraft flight in conditions of disturbances - Karimtaevna, Satybaldina Dana; Bekbolatovna, Amirzhanova Zinara; Assilkhanovna, Mashtayeva Aida (International Journal of Electrical and Computer Engineering (IJECE), 2022)
One of the most dangerous parts of the flight is the landing phase, as most accidents occur at this stage. In order to reduce the effect of the low-level wind shear on the longitudinal motion of the aircraft in the glide path landing mode (task) a robust H- control is proposed. Dynamic models of the plane and wind shear are built. H2 and H∞ synthesis methods are investigated for the task of aircraft flight control in a vertical plane during landing under conditions of undefined disturbances. Both control methods allow to reduce height deviation significantly. However, suboptimal control H∞ provides better quality of transition processes both in height and speed than optimal control H2. The results of simulation of the synthesized system confirm the effectiveness of H∞ - control for increasing robust stability to uncertainties caused by wind disturbances.